Impact of plant-based soil amendments on improvement of mortgaged Farmland (Bangladesh Journal of Botany, 2024)
A field experiment was conducted in Maoming, Guangdong, China to evaluate the effects of different plant-based soil amendments on soil quality, nutrient availability, plant growth, and land value. The application of plant-based soil amendments significantly increased the plant height, stem diameter, and biomass yield of corn, soybean, and rice crops. The greatest improvement was observed in corn crops, with a 12.6% increase in plant height, a 15% increase in stem diameter, and a 25.6% increase in biomass yield. Plant based soil amendments significantly improve soil quality, increase nutrient availability, and promote plant growth and productivity. Economic analysis shows that the use of plant-based soil amendments significantly increases the value of land, providing potential benefits for mortgage lenders and borrowers. This study emphasizes the importance of sustainable land use practices and the potential of plant-based soil improvement as an effective means of increasing land value.Bangladesh J. Bot. 53(3): 823-833, 2024 (September) Special